Body Temperature Measurement Techniques in Mammals of the Leporidae Family in Captive Environments (JBIOEDRA: Jurnal Pendidikan Biologi, 2025)
Mammals have two main mechanisms for maintaining body temperature: physiological and behavioral mechanisms. Rabbits, as members of the family Leporidae, are endothermic animals that are sensitive to changes in environmental temperature, making body temperature measurements important for assessing their physiological adaptation in captivity. This study aimed to analyze the comparison between environmental temperature and rectal temperature of male and female rabbits at two different locations in East Java, namely Malang City and Malang Regency. The research employed a quantitative approach, collecting rectal temperature data using a digital thermometer and environmental temperature data using an HTC-2 thermometer. Measurements were taken twice daily, in the morning and afternoon, over one month in May 2024. The results showed that the environmental temperature in Malang City (27.0–27.7?°C) was higher than in Malang Regency (22.6–25.3?°C), but both remained within the rabbits’ physiological tolerance limits. The rectal temperature of male and female rabbits ranged from 36.6–38.4?°C, which is still considered normal. T-Test analysis indicated significant differences in environmental temperature (p = 0.018–0.026) and rectal temperature (p = 0.002–0.050) between the two locations. It was concluded that both Malang City and Malang Regency are suitable for rabbit breeding, with the recommendation that future studies should take into account humidity, cage type, and a larger sample size for more comprehensive analysis.
Keywords: Leporidae, Mammals, Body temperature, Measurement, Captivity